Immunophenotypes of lymphocytes in prospectively followed up human papillomavirus lesions of the cervix. - Väyrynen, M (1985)
From 1981 286 women were prospectively followed up for a mean (SD) of 16 (14) months for established infection with human papillomavirus (HPV) with or without coexistent cervical intraepithelial neoplasia (CIN). The in situ immunocompetent cell infiltrates in 263 cervical punch biopsy specimens from these women were phenotypically identified by the avidinbiotin peroxidase complex (ABC) technique using monoclonal antibodies Leu-10, OKT-3, OKT-4, and OKT-8. Leu-10+ B lymphocytes far outnumbered the OKT-3+ T lymphocytes in all types of HPV lesions (flat, inverted, and papillomatous condylomas of the cervix). The ratio of OKT-4+ to OKT-8+ (T helper to T suppressor cells) was slightly reduced in HPV lesions with more severe CIN and correlated positively with the intensity of the immunocompetent cell infiltrate. The ratio of OKT-4+ to OKT-8+ cells was highest in the 47 (28.8%) patients with HPV lesions that regressed during follow up, somewhat lower in the 85 (52.1%) with persistent lesions, and lowest in the 31 (19.1%) with lesions showing clinical progression. The results are discussed in terms of the proposed immune surveillance functions attributed to immunocompetent cells in situ according to the mucosal associated lymphatic tissue (MALT) concept. The conclusion drawn is that a dynamic balance between the immunoregulatory cells and their subtypes is a prerequisite for the proper handling of intracellular infections of the mucosa, including that with HPV.